Meaning and pedagogical impact of class notes translated into Mandarin Chinese for scholars from China enrolled in research techniques traning - Tiffany L. Whitcomb; Jiafen Hu (Adult Education Research Conference, 2014)
We conducted a qualitative study to understand the meaning of translating class notes into Mandarin Chinese for Chinese students enrolled in our hands-on training program for biomedical techniques. To date, no studies have reported interventions to support researchers from China as they learn animal care and use techniques, particularly whether translating class materials into Mandarin Chinese fulfills a specific pedagogical need. Semi-structured interviews were conducted in order to collect rich, descriptive data. Interviews were transcribed and open coding was conducted by each researcher independently. Axial coding was performed in unison until a consensus for categories was reached. Several themes emerged from the findings: a) Pedagogical impacts that ranged from time-saving to a distraction from learning English, b) Range in personal meaning from positive to negative, depending on English proficiency and degree of adaptation to U.S. culture, and c) Recommendations for supporting a variety of learning styles. While the translated documents saved time and clarified meaning for researchers new to the United States, these documents were offensive to those who reported being more proficient in English. Interestingly, most participants suggested that particular attention should be placed on the social aspects of teaching and learning. Therefore, our translated documents failed to address some pedagogical obstacles for Chinese scholars including listening and speaking English, adapting to different social environment in the US classroom and culture shock. As a result of this study, we have shifted the focus of our hands-on training program away from content and toward cultural competence for teachers.